2001
DOI: 10.1007/s002130100697
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned antinociception and freezing using electrical stimulation of the dorsal periaqueductal gray or inferior colliculus as unconditioned stimulus are differentially regulated by 5-HT2A receptors in rats

Abstract: 1) Conditioned freezing may be produced using the electrical stimulation of the dPAG or IC as unconditioned stimuli, 2) only the pairing of CS plus dPAG but not with IC stimulation, produces significant conditioned antinociception, 3) blockade of 5-HT2A receptors inhibits conditioned antinociception but not the conditioned defensive behavior using the electrical stimulation of the dPAG as unconditioned stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 56 publications
5
26
0
6
Order By: Relevance
“…The pattern of results obtained in the present experiments parallels those from typical avoidanceescape procedures, which utilize electric shock as the UCS, for example, an auditory stimulus paired with foot shock elicits classical conditioned responses (LeDoux et al, 1986(LeDoux et al, , 1990. From the anatomo-functional viewpoint, the IC may be associated with the processing of aversive conditioned stimuli and, for extension, with conditioned fear Castilho and Brandão, 2001). Therefore, the present results are in line with recent evidence obtained in this laboratory that has shown that rats learn to avoid the IC stimulation when the warning stimulus is a light and not a tone (Troncoso et al, 1998).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The pattern of results obtained in the present experiments parallels those from typical avoidanceescape procedures, which utilize electric shock as the UCS, for example, an auditory stimulus paired with foot shock elicits classical conditioned responses (LeDoux et al, 1986(LeDoux et al, , 1990. From the anatomo-functional viewpoint, the IC may be associated with the processing of aversive conditioned stimuli and, for extension, with conditioned fear Castilho and Brandão, 2001). Therefore, the present results are in line with recent evidence obtained in this laboratory that has shown that rats learn to avoid the IC stimulation when the warning stimulus is a light and not a tone (Troncoso et al, 1998).…”
Section: Discussionsupporting
confidence: 78%
“…Latent inhibition has been considered as a model for information filtering processesand demonstrates attentional processes in rats that are responsive to drug treatment in a fashion that parallels drug responses seen in humans with schizophrenia (Makintosh, 1975;Lubow et al, 1982;Dunn et al, 1993;Sandner et al, 2002). We have already shown that stimulation of neural circuits in the central nucleus of the IC supports Pavlovian conditioning and that latent inhibition may be demonstrated using stimulation of these neural circuits in the IC as negative reinforcement Troncoso et al, 1998;Castilho and Brandão, 2001).…”
Section: Introductionmentioning
confidence: 94%
“…A single electrical stimulation of the dPAG at the escape threshold does not lead to any context conditioning. In fact, at least two sessions of pairings of dPAG electrical stimulation environmental stimuli are required to produce contextual fear conditioning (Castilho et al 2001). …”
Section: Vianna Et Almentioning
confidence: 99%
“…Recently, it has been shown that 5-HT 2A receptors alone mediate fear and anxiety states (Castilho and Brandao, 2001;Weisstaub et al, 2006) and that activation of 5-HT 2A receptors improves learning and working memory (Williams et al, 2002;Harvey, 2003;Harvey et al, 2004;Romano et al, 2006). Also, 5-HT is involved in the control of both cardiovascular and acute psychological stress reactivity (Davies et al, 2006).…”
Section: Introductionmentioning
confidence: 99%